Supervision of the Village Consultative Body (BPD) in Infrastructure Development in Indari Village, West Bacan District South Halmahera Regency - Supriyanto Busra; Ali Lating; Rahmad Suaib (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2023)
Abstract The implementation of Village Development will run well, which is largely determined by the level of supervision of the Supervisory institution, one of which is the Village Consultative Body (BPD). The main task is to ensure that every development implementation runs well from the planning to evaluation and accountability aspects. BPD supervision is also important so that development implementation is in accordance with the determined goals and benefits. The method used in this research is a descriptive qualitative method. The data sources used are primary data such as the village head, BPD chairman, deputy chairman and members, as well as community leaders who are considered to have the ability to assess the program being implemented. Secondary data is in the form of planning and budgeting documents. which has been agreed upon by the village government and BPD. Data collection techniques are observation, interviews and documentation. And the use of data analysis techniques in research is an analysis technique, namely data reduction, data presentation and drawing conclusions or verification The results of the research show that BPD supervision in the implementation of infrastructure in Indari Village in 2023 is carried out directly, including the program for building concrete fences, building toilets and building clean water. This is intended to find out more deeply about the development of the program, both in terms of time, budget realization and targeted targets. must be fulfilled in accordance with the plan that has been agreed upon in development planning. The implementation of coordination in the development program is quite good between the village government and the BPD, especially related to the program implementation process until the program ends. A number of obstacles faced include: budget delays in the disbursement process due to technical obstacles.